Chemovirotherapy for head and neck squamous cell carcinoma with EGFR-targeted and CD/UPRT-armed oncolytic measles virus - Plath, Karim; Bossow, Sascha; Großardt, Christian; Leber, Mathias Felix; Springfeld, Christoph; Plinkert, Peter K.; Kalle, Christof von; Ungerechts, Guy (Cancer gene therapy, 2012)
First-line treatment of recurrent and/or refractory head and neck squamous cell carcinoma (HNSCC) is based on platinum, 5-fluorouracil (5-FU) and the monoclonal antiEGFR antibody cetuximab. However, in most cases this chemoimmunotherapy does not cure the disease, and more than 50% of HNSCC patients are dying because of local recurrence of the tumors. In the majority of cases, HNSCC overexpress the epidermal growth factor receptor (EGFR), and its presence is associated with a poor outcome. In this study, we engineered an EGFR-targeted oncolytic measles virus (MV), armed with the bifunctional enzyme cytosine deaminase/uracil phosphoribosyltransferase (CD/UPRT). CD/UPRT converts 5-fluorocytosine (5-FC) into the chemotherapeutic 5-FU, a mainstay of HNSCC chemotherapy. This virus efficiently replicates in and lyses primary HNSCC cells in vitro. Arming with CD/UPRT mediates efficient prodrug activation with high bystander killing of non-infected tumor cells. In mice bearing primary HNSCC xenografts, intratumoral administration of MV-antiEGFR resulted in statistically significant tumor growth delay and prolongation of survival. Importantly, combination with 5-FC is superior to virus-only treatment leading to significant tumor growth inhibition. Thus, chemovirotherapy with EGFR-targeted and CD/UPRT-armed MV is highly efficacious in preclinical settings with direct translational implications for a planned Phase I clinical trial of MV for locoregional treatment of HNSCC.